Hyperactive Follicular Helper T Cells Contribute to Dysregulated Humoral Immunity in Patients With Liver Cirrhosis - Zhao, Juanjuan; Shi, Jijing; Qu, Mengmeng; Zhao, Xin; Wang, Hongbo; Huang, Man; Liu, Zhenwen; Li, Zhiwei; He, Qing; Zhang, Shuye; Zhang, Zheng (Frontiers in Immunology, 2019)
Objectives: Liver cirrhosis (LC) is usually accompanied by cirrhosis associated immune dysfunction (CAID) including the reduced naïve T cells and memory B cells. However, little is known regarding on follicular helper T (Tfh) cell compartments in cirrhotic patients, especially in the secondary lymphoid organs such as spleen. This study characterizes splenic Tfh cells and explores its association with humoral immunity and disease progression in cirrhotic patients. Methods: Using flow cytometry and histological staining, we analyzed the frequency and cytokine production of splenic Tfh cells from LC patients and healthy controls (HCs). Co-culture experiments of sorted Tfh and B cells were performed for functional analysis in vitro. The correlations between Tfh cells and disease progression markers as well as B cell subset perturbations were also examined. Results: PD-1highICOS+CXCR5+ Tfh cells were preferentially enriched in spleen of cirrhotic patients, where they expressed higher levels of CXCR3 and produced more interleukin (IL)-21. Histologically, more splenic Tfh cells occupied the B cell follicular structure in LC patients where they shaped more active germinal centers (GCs) than those in HC spleens. In vitro, splenic Tfh cells in cirrhotic patients robustly induce plasma cell differentiation through IL-21 dependent manner. Finally, increased Tfh cell levels positively correlate with the plasma cell levels and disease severity in LC patients. Conclusions: We conclude that hyperactive Tfh cells contribute to dysregulated humoral immunity in patients with liver cirrhosis.